The benefit and risk of addition of PD-1/PD-L1 inhibitors to chemotherapy for advanced cervical cancer: a phase 3 randomized controlled trials based meta-analysis - Deping Luo; Ying Yu; Qi Wang; Tao Peng; Chan Li; Wenxiong Zhang; Jing Huang (BMC Cancer)
Abstract Background Chemotherapy has been confirmed as an effective treatment for advanced cervical cancer. However, whether combining PD-1/PD-L1 inhibitors with chemotherapy (PIC) offers superior efficacy remains a subject of debate. This meta-analysis aims to compare the antitumor effects and safety profile of PIC versus chemotherapy. Methods We conducted a comprehensive search across six databases to identify eligible randomized controlled trials (RCTs). The primary outcomes assessed were overall survival (OS) and progression-free survival (PFS), while the secondary endpoints included response rates and adverse events (AEs). Results Four RCTs (BEATcc, CALLA, KEYNOTE-826, and KEYNOTE-A18) analyzing 2,857 patients were included. The PIC regimen notably enhanced OS (hazard ratio [HR]: 0.70 [0.61, 0.80], P < 0.00001), PFS (HR: 0.69 [0.61, 0.77], P < 0.00001), objective response rate (ORR) (risk ratio [RR]: 1.11 [1.02, 1.22], P = 0.02), and disease control rate (DCR) (RR: 1.05 [1.01, 1.08], P = 0.004). Improvements in OS and PFS for the PIC group were evident across nearly all subgroups. Moreover, the survival benefit for the PIC group increased with longer patient survival and elevated PD-L1 expression. The PIC group encountered higher rates of grade 3–5 AEs, and serious AEs. The top 5 grade 3–5 AEs were anemia (19.47%), hypertension (12.65%), decreased white blood cell count (11.76%), decreased neutrophil count (11.38%), and neutropenia (10.99%). Conclusions The PIC regimen appears superior to chemotherapy alone for advanced cervical cancer (metastatic/recurrent or locally advanced), demonstrating improved survival and response rates. However, the associated increase in AEs warrants careful consideration in its clinical application.